1996
DOI: 10.1093/rheumatology/35.7.695
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapy and Occupational Therapy for Juvenile Chronic Arthritis: Custom and Practice in Five Centres in the Uk, Usa and Canada

Abstract: Physiotherapy and occupational therapy are widely accepted as being of central importance for the treatment of juvenile chronic arthritis (JCA). However, these approaches have rarely been subject to critical scrutiny. The aims of this report are to highlight some of the inter-centre similarities and differences observed in the implementation of physical and occupational therapy for JCA, and to emphasize the need for scientifically controlled research in this area. During a series of visits to several paediatri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
4

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 0 publications
1
10
0
4
Order By: Relevance
“…The effi cacy of these interventions is unclear, although Brostrom et al (2004) reported a modest (6%) increase in walking speed following intra-articular corticosteroid injections, and Powell et al (2005) demonstrated the benefi ts of customized orthoses over prefabricated insoles or supportive athletic shoes for improving foot pain and function. Where necessary, input from other disciplines, including physiotherapy and occupational therapy (Hackett et al, 1996), may be of value to these children, but these were not accounted for in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The effi cacy of these interventions is unclear, although Brostrom et al (2004) reported a modest (6%) increase in walking speed following intra-articular corticosteroid injections, and Powell et al (2005) demonstrated the benefi ts of customized orthoses over prefabricated insoles or supportive athletic shoes for improving foot pain and function. Where necessary, input from other disciplines, including physiotherapy and occupational therapy (Hackett et al, 1996), may be of value to these children, but these were not accounted for in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions such as splinting and foot orthoses can correct deformities and malalignments and decrease pain (65). Several studies have shown that children with polyarticular JIA are less active than their healthy counterparts and exhibit reduced aerobic and anaerobic exercise capacity (66,67).…”
Section: Physical Therapy and Sleep Interventionsmentioning
confidence: 99%
“…Water may be the only medium whereby some patients feel on an equal footing with their peers and exercise programmes can become a family activity. 8 Although hydrotherapy is commonly used in JIA, 28 little scientific evidence exists to support the use of this modality of treatment. Verhagen and colleagues published a systematic review assessing the effects of hydrotherapy (balneotherapy) for rheumatoid arthritis and osteoarthritis.…”
Section: Consequences Of Pathophysiology Of Jiamentioning
confidence: 99%